A synthesis method for first-order active disturbance rejection controllers: Procedures and field tests. (October 2022) - Wu, Zhenlong; Makeximu,; Yuan, Jie; Liu, Yanhong; Li, Donghai; Chen, YangQuan
Abstract: Active disturbance rejection control (ADRC) is getting explosive attention with many advantages. This paper proposes a synthesis method for the first-order ADRC based on the existing PI controller. Firstly, the relationship between the first-order ADRC and PI controller is derived. Then the initial parameters of ADRC can be obtained directly from the existing PI parameters and the synthesis procedure is summarized. Moreover, the parameter constraints to obtain better control performance are acquired based on theoretical analyses and ADRC parameters can be optimized based on these parameter constraints. The effectiveness of the proposed ADRC synthesis method and the parameter optimization method is validated by simulations and comparative experiments. Finally, the proposed methods are applied to the secondary air system of a power plant and running data indicate that ADRC can improve the control performance evidently. Highlights: The synthesis method of the first-order ADRC from the existing PI controller is proposed. The parameter constraints to further optimize ADRC are analyzed theoretically. The effectiveness of the proposed synthesis method is validated by field applications.